Expanding Health Coverage for Vulnerable Groups in India - Nagpal, Somil (World Bank, Washington, DC, 2013)
India's health sector continues to be challenged by overall low levels of public financing, entrenched accountability issues in the public delivery system, and the persistent dominance of out-of-pocket spending. In this context, this case study describes three recent initiatives introduced by the central and state governments in India, aimed at addressing some of these challenges and improving the availability of and access to health services, particularly for the poor and vulnerable groups in the country. This includes two federal schemes introduced by the Government of India-the National Rural Health Mission (NRHM) of the Ministry of Health and Family Welfare and the Rashtriya Swasthya Bima Yojana (RSBY) of the Ministry of Labor and Employment-and the Rajiv Aarogyasri scheme launched by the state government of Andhra Pradesh. The three schemes discussed in this case study were designed and implemented by different agencies almost in parallel, over the same time period, and used different financing and delivery approaches. A discussion of the mechanics and operational features of these programs has been undertaken to unravel the underlying complexities, interactions, and interdependencies of these programs within the country's health system. The remainder of this case study on India's march toward universal health coverage focuses on three recent, prominent programs, and includes a discussion on the institutional structure of these programs and their interactions within the country's health system, their mechanisms for beneficiary targeting and enrolment, the benefits packages covered by them, accompanying innovations in public financial management, and their information environment. Annex one presents an overview of the health system and health financing in India, and annex two discusses the evolutionary context of India's Government sponsored health insurance schemes. The discussion of the mechanics and operational features of these programs has been undertaken to unravel the underlying complexities, interactions, and interdependencies within these programs. The case study also aims to contribute to the ongoing debate within the Indian health sector, with opinions divided between investments in traditional input-based health spending for publicly managed health facilities versus demand-side financing, purchasing of care, and involving private providers and intermediaries in delivering services financed by public money. The case study also aims to share how the lessons learned by one program can be applicable more widely within the Indian health system and beyond